Description Of School Well-Being on Students Of Senior High School: Gambaran School Well-Being pada Siswa Sekolah Menengah Atas - Edwin Oktaviyanto; Ramon Ananda Paryontri (Universitas Muhammadiyah Sidoarjo, 2022)
This descriptive quantitative study investigates the phenomenon of school well-being among 279 students in SMK 10 November Sidoarjo. The research aims to provide an explanation of school well-being and its implications. Proportionate stratified random sampling was employed to select the subjects, and data were collected using a Likert scale. Data analysis using SPSS 26.0 and Excel revealed that the students' school well-being fell within the medium category (70%), with a small proportion experiencing low (16%) and high (14%) levels. These findings indicate that students possess the ability to cultivate a sense of well-being during their learning process, leading to enhanced comfort. The study contributes to our understanding of school well-being and emphasizes the importance of nurturing positive learning environments for students' overall well-being. Highlights: School well-being: This study focuses on understanding the level of school well-being experienced by students. Quantitative analysis: The research utilizes a descriptive quantitative approach to analyze data collected from 279 students. Learning environment and comfort: The results highlight the significance of creating positive learning environments that contribute to students' comfort and overall well-being. Keywords: school well-being, student perspectives, quantitative analysis, learning environment, comfort